THE IMPACT OF LOAN-TO-VALUE RATIO POLICY IMPLEMENTATION AND ADJUSTMENTS ON CONVENTIONAL BANKÃâÃâS PERFORMANCE IN INDONESIA - Alfathan Tuba (NIM 19014099), Loudy
ABSTRACT The aim of this study is to identify (1) the before and after impact of Loan-to-Value (LTV) ratio policy implementation on conventional bank performance in Indonesia, (2) the before and after impact of LTV ratio policy adjustments in 2013, 2015, and 2016 on conventional bank in Indonesia, and (3) the effectiveness and significance of LTV ratio policy in affecting conventional bank performance in Indonesia. The variables used as indicators of bank performance in this research are Non-Performing Loan Ratio (NPL) and Loan-to-Deposit Ratio (LDR), which align with Bank Indonesia perspective as macro prudential decision maker. The subjects of this research are all conventional banks registered in the financial statements of the Financial Services Authority (OJK) and Bank Indonesia. The data collection in this research is derived entirely from Indonesian Banking Statistics (SPI) which is released on the official OJK website on a monthly basis from January 2008 to December 2016. Furthermore, data analysis was performed using T-Test: Paired Two Sample for Means for both ratios with a total of 108 data for each ratio analysis. And overall, research results show that (1) LTV proven to be able to significantly reduce banking risk, specifically on commercial bank system, (2) proven to be able to significantly increase commercial bank industry LDR, while still maintaining ideal liquidity proportion, (3) proven to be able to significantly increase banking risk if the purpose is relaxation, and (4) it adjustment in 2013, 2015, and 2016 are not statistically effective in affecting bank performance. Keywords: Loan-to-Value Ratio Policy, Bank Performance, NPL, and LDR.